RECONSTRUCTION OF THE REGULATION ON LAW ENFORCEMENT AGAINST PERPETRATORS OF ELECTORAL CRIMES IN ACHIEVING LEGAL CERTAINTY - Eno, La Radi (ANAYASA : Journal of Legal Studies, 2026)
This study aims to analyze and reconstruct the regulation of law enforcement against perpetrators of electoral crimes in order to achieve legal certainty. The research method employed is normative legal research using statutory, conceptual, and case approaches. The legal materials consist of primary, secondary, and tertiary sources, which are analyzed qualitatively. The findings indicate that the current regulation of law enforcement for electoral crimes has not fully reflected the principles of legal certainty, justice, and expediency. The weaknesses of these regulations are evident in the substantive regulation of electoral criminal law, the law enforcement mechanisms that have not been optimally integrated, and the overlapping authorities between election management bodies and law enforcement institutions. Therefore, a reconstruction of the regulation of law enforcement for electoral crimes is required, emphasizing the clarity of legal norms, the strengthening of law enforcement institutions, and the harmonization of laws and regulations. The regulatory reconstruction proposed in this study is expected to realize legal certainty in the enforcement of electoral crime laws, while also strengthening the quality of democracy and the implementation of the rule of law in Indonesia.